ANALISIS KOLABORASI GURU DAN ORANG TUA DALAM PEMBELAJARAN IPA JARAK JAUH - Rahmat Syah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes the collaboration between teachers and parents through distance learning in natural science education and analyzes the role of elementary school teachers. The method used was a survey with a sample of 48 student parents. Data analysis used quantitative analysis, which emphasized the influence of the teacher's and parents’ role on the successful natural science learning at school for school-age children. Data analysis showed that the correlation value between the teacher's role variable and students’ learning outcomes was 0.635 and the t-count value was higher than the t-table. Hence, it could be said that there was an influence between the teacher's role and the student’s success in the classroom. The correlation value of the parent's role on students’ learning success was 0.375 and the t-count value was 2.582, which meant that it was higher than the t-table. Therefore, it could be ascertained that the influence of the parent's role on students’ success in learning was significant. The results of the measurements indicated that there was an influence of the role of teachers and parents on students’ success in school-age children's education in natural science learning. Understanding of scientific concepts was still rigid by following reference books, limited tools, materials, and time, and the implementation of science concepts did not yet refer to the environment of school-age children. Based on the results, it could be resumed that the collaboration of teachers and parents needed to be improved in accordance with the teaching purposes of natural science learning subjects for school-age children to improve online and distance learning.